The GluN3-containing NMDA receptors - Kunlong Xiong; Shulei Lou; Zuoyu Lian; Yunlin Wu; Zengwei Kou (Channels)
N-methyl-D-aspartate receptors (NMDARs) are heterotetrameric ion channels that play crucial roles in brain function. Among all the NMDAR subtypes, GluN1-N3 receptors exhibit unique agonist binding and gating properties. Unlike “conventional” GluN1-N2 receptors, which require both glycine and glutamate for activation, GluN1-N3 receptors are activated solely by glycine. Furthermore, GluN1-N3 receptors display faster desensitization, reduced Ca2+ permeability, and lower sensitivity to Mg2+ blockage compared to GluN1-N2 receptors. Due to these characteristics, GluN1-N3 receptors are thought to play critical roles in eliminating redundant synapses and pruning spines in early stages of brain development. Recent studies have advanced pharmacological tools for specifically targeting GluN1-N3 receptors and provided direct evidence of these glycine-activated excitatory receptors in native brain tissue. The structural basis of GluN1-N3 receptors has also been elucidated through cryo-EM and artificial intelligence. These findings highlight that GluN1-N3 receptors are not only involved in essential brain functions but also present potential targets for drug development.